2014
DOI: 10.1089/fpd.2013.1629
|View full text |Cite
|
Sign up to set email alerts
|

NontyphoidalSalmonellaInfection in Children with Acute Gastroenteritis: Prevalence, Serotypes, and Antimicrobial Resistance in Shanghai, China

Abstract: Information about nontyphoidal Salmonella (NTS) infection in children is limited in mainland China. The objective of this study was to investigate the prevalence, serotypes, and antibiotic resistance patterns of NTS infection in children in Shanghai. All cases with probable bacterial diarrhea were enrolled from the enteric clinic of a tertiary pediatric hospital between July 2010 and December 2011. Salmonella isolation, serotyping, and antimicrobial susceptibility testing were conducted by the microbiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
43
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 28 publications
17
43
5
Order By: Relevance
“…SGI1 carries resistance genes blaPSE-1, floR, aadA, sul, and tet encoding the resistance feature to ampicillin, chloramphenicol, streptomycin, sulfonamide, and tetracycline, respectively (phenotype ACSSuT) [44]. In our study, the prevalence of ACSSuT in 1,4, [5],12:i:-, S. Typhimurium, and S. Choleraesuis was significantly higher than in S. Enteritidis; this is similar to findings in Shanghai [9]. Data from Switzerland [40] Statistical analysis of ≥ 3 clinically important antimicrobial agents showed that S. Choleraesuis was the most resistant Salmonella isolate, and that extended-spectrum cephalosporin is the best drug to treat Salmonella infections.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…SGI1 carries resistance genes blaPSE-1, floR, aadA, sul, and tet encoding the resistance feature to ampicillin, chloramphenicol, streptomycin, sulfonamide, and tetracycline, respectively (phenotype ACSSuT) [44]. In our study, the prevalence of ACSSuT in 1,4, [5],12:i:-, S. Typhimurium, and S. Choleraesuis was significantly higher than in S. Enteritidis; this is similar to findings in Shanghai [9]. Data from Switzerland [40] Statistical analysis of ≥ 3 clinically important antimicrobial agents showed that S. Choleraesuis was the most resistant Salmonella isolate, and that extended-spectrum cephalosporin is the best drug to treat Salmonella infections.…”
Section: Discussionsupporting
confidence: 87%
“…S. Enteritidis is the most frequently isolated Salmonella serotype in our local area, so we should pay attention to its features. The 9% rate of resistance to ceftriaxone in this study was higher compared to < 1% in Spain in 2007-2009 [28], similar to data from Shanghai [9], and lower compared to the 50%-60% E. coli rates in the local area [29]. It is different from Europe and America where TEM and SHV is the main type of ESBL; CTX-M is prevalent in Asia, generally.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Multidrug resistance has been associated with a higher risk of invasive infection, higher frequency and duration of hospitalisation and increased risk of death as compared to infections caused by susceptible strains. 40,41 In addition, from 2000, several studies have shown a decreased susceptibility to fluoroquinolones, drugs of choice for treatment of invasive gastrointestinal infections, in many parts of the world. [42][43][44] According to data reported by WHO, fluoroquinolone resistance in NTS is lower in the European region, while it is much higher in some countries of Africa (30%-35%), of Eastern Mediterranean region (46%-49%) and in Peru (96%).…”
Section: Non-typhoidal Salmonella (Nts)mentioning
confidence: 99%